The transcriptional repressor Ctbp2 as a metabolite sensor regulating cardiomyocytes proliferation and heart regeneration - Yanting Meng; Jianwen Ding; Yanping Wang; Jing Wang; Wei Huang; Wenkang Jiang; Jiayi Li; Xiujuan Lang; Sifan Zhang; Yumei Liu; Xijun Liu; Hulun Li; et al. (Molecular Medicine)
Abstract Background C-terminal binding protein-2 (Ctbp2) is an evolutionarily conserved transcriptional repressor that regulates fundamental processes such as cell proliferation and apoptosis. However, the potential role of Ctbp2 in cardiomyocyte proliferation and heart regeneration remains unclear. In this study, we aim to explore the important role of Ctbp2 in cardiomyocyte proliferation and the regeneration of injured adult hearts. Methods and results In this study, we found that the expression of Ctbp2 in cardiomyocytes is downregulated after adulthood. Silencing Ctbp2 in cardiomyocytes on the post-natal day 1 (P1) reduced the proliferation ability of cardiomyocytes, whereas overexpressing Ctbp2 enhanced the proliferation ability of cardiomyocytes. Additionally, overexpressing Ctbp2 via adeno-associated virus-9 (AAV9) had no effect on the hearts of normal adult mice, but in the case of heart injury, overexpression of Ctbp2 in adult mice cardiomyocytes promoted cardiomyocyte proliferation. Mechanistically, the transcriptional repressor Ctbp2 acts as a metabolite sensor, and its regulation of cardiomyocyte proliferation is influenced by the metabolites NADH/NAD+ and fatty acyl-CoAs. Ctbp2 is activated by the intracellular accumulation of NADH during cardiomyocyte ischemia and hypoxia, inhibiting the transcriptional activity of the transcription factor FoxO1, thereby repressing the expression of the target genes and cell cycle negative regulators p21 and p27, allowing cardiomyocytes to re-enter the cell cycle. In contrast, normal adult cardiomyocytes mainly use fatty acid oxidation metabolism as their primary energy source, and the intracellular production of fatty acyl-CoAs inactivates Ctbp2, thus preventing it from inhibiting FoxO1 mediated cell cycle arrest. Conclusion In conclusion, this study demonstrates that the Ctbp2-FoxO1-p21/p27 axis can promote cardiomyocyte proliferation and heart regeneration. As a metabolite sensor, Ctbp2 is activated during cardiomyocyte ischemia and hypoxia, while it is inactivated under normal conditions. This controllable and transient regulation of cardiomyocyte proliferation can avoid the detrimental effects on cardiac function caused by long-term regulation of cardiomyocyte proliferation, such as hypertrophic cardiomyopathy or heart failure. This provides new targets and new ideas for addressing the issues of cardiomyocyte proliferation and heart regeneration.